1999
DOI: 10.1074/jbc.274.47.33510
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Binding to Monomeric Light-harvesting Complex

Abstract: The chromophore binding properties of the higher plant light-harvesting complex II have been studied by site-directed mutagenesis of pigment-binding residues. Mutant apoproteins were overexpressed in Escherichia coli and then refolded in vitro with purified chromophores to yield holoproteins selectively affected in chlorophyll-binding sites. Biochemical and spectroscopic characterization showed a specific loss of pigments and absorption spectral forms for each mutant, thus allowing identification of the chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
199
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(234 citation statements)
references
References 34 publications
31
199
2
1
Order By: Relevance
“…Considering that the 675-nm band is the only negative contribution observed in the spectra, it can be concluded that the monomers are isoenergetics. Similar values for the absorption of monomeric Chl A5 were found in LHCII and CP29 (21,22), thus supporting the present conclusion. We have to highlight the fact that the bandwidth of the red-most transition is very large, as is expected in the case of a Chl dimer because of strong electronphonon coupling, whereas the absorption at 675 nm has the FWHM typical of a Chl monomer.…”
Section: Is the Presence Of Asn As Ligand For Chl A5 Sufficient To Lesupporting
confidence: 80%
See 3 more Smart Citations
“…Considering that the 675-nm band is the only negative contribution observed in the spectra, it can be concluded that the monomers are isoenergetics. Similar values for the absorption of monomeric Chl A5 were found in LHCII and CP29 (21,22), thus supporting the present conclusion. We have to highlight the fact that the bandwidth of the red-most transition is very large, as is expected in the case of a Chl dimer because of strong electronphonon coupling, whereas the absorption at 675 nm has the FWHM typical of a Chl monomer.…”
Section: Is the Presence Of Asn As Ligand For Chl A5 Sufficient To Lesupporting
confidence: 80%
“…It has to be considered that the His versus Asn substitution appears to be a usual tool for modulation of Chl-Chl interactions in Lhc proteins; Chl A2, when coordinated by Asn in Lhcb1, establishes excitonic interactions with neighbor pigments, namely Chl B2 and Chl A4. This interaction is absent in Lhcb4 (CP29) in which His is the ligand for Chl A2 (21,22) and again present in the Asn-bearing Lhcb5 (CP26), whose overall biochemical and spectral characteristics are very close to those of CP29 (19).…”
Section: Is Asn As Ligand For Chl A5 Necessary To Yield To the Low mentioning
confidence: 96%
See 2 more Smart Citations
“…Two positive bands at 662 and 686 nm accompany the negative band at 675 nm, and the asymmetry of the positive band at 686 nm suggests that the bands at 662 and 686 nm arise from a blue shift and a broadening of the 675 nm band. The 675 nm absorption in the trimeric LHCII is most likely from either Chl a 4 or Chl a 5 (52), which appear to be in close proximity to Lut2 (53). Thus, these differences in absorption spectrum between LHCII trimers and monomers can tentatively be attributed to a change in the Lut2/ Chl a 4 /Chl a 5 domain occurring upon monomerization.…”
Section: Pigment Composition Of Monomeric Lhciimentioning
confidence: 92%